2001
DOI: 10.1046/j.1365-2389.2001.00385.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lanthanum and mixtures of rare earths on ammonium oxidation and mineralization of nitrogen in soil

Abstract: SummaryRare earths are applied widely in Chinese agriculture to improve crop nutrition and incidentally in fertilizers, yet little is known of their effect on the biological functioning of the soil. We have studied the effects of lanthanum and of mixtures of rare earths on the potential ammonium oxidation and nitrogen mineralization in soil by incubation experiments in the laboratory. The no-observed-effect and median effective concentrations of the rare earths on these two processes are reported, and their co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…It is thus a reasonable hypothesis that for effects on soil organisms that affect soil productivity and ecotoxicity, all non-radioactive lanthanides can be assumed to be equally effective on a molar basis. This is consistent with the findings of Xu and Wang (2001) that the influence of individual rare earths in mixtures on two discussed microbial processes can be additive. It does not exclude the possibility that different lanthanides have different effectiveness under other circumstances, as exemplified for luminescence of monocellular organisms.…”
Section: Effect Concentrations For Soil Organismssupporting
confidence: 92%
See 1 more Smart Citation
“…It is thus a reasonable hypothesis that for effects on soil organisms that affect soil productivity and ecotoxicity, all non-radioactive lanthanides can be assumed to be equally effective on a molar basis. This is consistent with the findings of Xu and Wang (2001) that the influence of individual rare earths in mixtures on two discussed microbial processes can be additive. It does not exclude the possibility that different lanthanides have different effectiveness under other circumstances, as exemplified for luminescence of monocellular organisms.…”
Section: Effect Concentrations For Soil Organismssupporting
confidence: 92%
“…From pot studies of ammonium oxidation and mineralization of nitrogen by microorganisms, Xu and Wang (2001) concluded that the influence of individual rare earth elements in the mixtures on the two processes could be additive.…”
Section: Appendixmentioning
confidence: 99%
“…Rare earth elements uptake by plants is not only controlled by the plant itself but depends on their content in soil, soil water pool, and other minerals (Weltje et al 2002, Brioschi et al 2013. Water-soluble and exchangeable fractions of REE are the most available (Li et al 1998, Cao et al 2000, Xu and Wang 2001, Redling 2006. Other sources include silicate particles in soil (Fu et al 2000, Fu et al 2001 and airborne particles (averaging less than 2.5 µm) or gasses absorbed by vegetation Zhao 1994, Peresedov andGundorina 1997).…”
Section: Factors Affecting Ree Absorption and Transportmentioning
confidence: 99%
“…2326 Nitrification capacity is also an important measure of soil fertility; Xu and Wang (2001) studied the effect of an REE mixture (a commercial preparation for agricultural use) and La on ammonia oxidation in soil slurries. 27 They reported no observed effect concentrations of 393 and 432 mg kg −1 for the mixture and La, respectively, and concluded that REE fertilizer additions did not significantly impact soil health. However, REE speciation and concentrations were not examined.…”
Section: Introductionmentioning
confidence: 99%